A study on the bio-applicability of aqueous-dispersed van der Waals 1-D material Nb2Se9 using poloxamer - Chae, Sudong; Oh, Seungbae; Choi, Kyung Hwan; Lee, Jin Woong; Jeon, Jiho; Liu, Zhixiang; Wang, Cong; Lim, Changmo; Dong, Xue; Woo, Chaeheon; Asghar, Ghulam; Shi, Liyi; et al. (Scientific Reports, 2021)
In this research, dispersion of a new type of one-dimensional inorganic material Nb2Se9, composed of van der Waals bonds, in aqueous solution for bio-application study were studied. To disperse Nb2Se9, which exhibits hydrophobic properties in water, experiments were carried out using a block copolymer (poloxamer) as a dispersant. It was confirmed that PPO, the hydrophobic portion of Poloxamer, was adsorbed onto the surface of Nb2Se9, and PEO, the hydrophilic portion, induced steric hinderance to disperse Nb2Se9 to a size of 10 nm or less. To confirm the adaptability of muscle cells C2C12 to the dispersed Nb2Se9 using poloxamer 188 as dispersant, a MTT assay and a live/dead assay were performed, demonstrating improvement in the viability and proliferation of C2C12 cells.